Scientometric Study of Astronomy and Astrophysics Research in India (1994 – 2015): An Analysis from Astrophysics Data System - Kumar Rai, Vijay; Sengar, K. P. S.; Cyriac, Giji (Journal of Information and Knowledge, 2019)
A scientometric study evaluation of India’s scientific research output in the field of astronomy and astrophysics during 1994–2015 has been done. The bibliographic data were harvested from Astrophysics Data System Database (ADSD) for a period of 22 years from 1994 to 2015. The compound annual growth rate, collaboration trends, authorship pattern, growth rate and doubling time, degree of collaboration, highly productive authors are examined. India is holding 15th rank in the field of astronomy and astrophysics research in the world and it is found that 9.09% was the average CAGR of Indian astronomy and astrophysics publications during the study period. It is also found that India has published 83.67% of research papers as journal articles, 11.88% publication as conference papers. The degree of collaboration is 0.86. The study revealed that collabor ative research is most preferred and focused as multi authorship pattern of publication; 3815 papers were two–authored followed by 3250 papers with three–authors during the study period.